Phytochemical, antioxidant, in silico, and in vitro anti-breast cancer effects of Erigeron sumatrensis from Gayo Highlands (Indonesia) against MCF-7 cells - VIVIVERA RUSELLI PUSPA; MUHAMMAD ANSARI ADISTA; DJUFRI DJUFRI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Puspa VR, Adista MA, Djufri. 2024. Phytochemical, antioxidant, in silico, and in vitro anti-breast cancer effects of Erigeron sumatrensis from Gayo Highlands (Indonesia) against MCF-7 cells. Biodiversitas 25: 5123-5137. This study investigated the therapeutic potential of Erigeron sumatrensis, a wild herb from the Gayo Highlands, by evaluating its methanol stem extract's phytochemical profile, antioxidant activity, biological activity, molecular docking, ADMET prediction, and MTT assay using MCF-7 cells. Phytochemical analysis revealed the presence of various secondary metabolites, including flavonoids, phenolics, terpenoids, steroids, tannins, and alkaloids. The stem extract exhibited the highest total phenolic content at 959.091 mgQE/g. Antioxidant activity, assessed using the DPPH assay, was strong with an IC50 value of 96 ?g/mL. Gas chromatography-mass spectrometry analysis of the methanol extract of E. sumatrensis stems led to the identification of 24 compounds. Molecular docking studies identified three compounds-Stigmast-7-en-3-ol, (3?,5?,24S)-, Caryophyllene oxide and 1H-Cycloprop[e]azulen-7-ol, decahydro- 1,1,7-trimethyl-4-methylene-, [1ar(1a?,4a?,7?,7a?,7b?)] exhibiting potential anti-proliferative activity against MCF-7 cells. ADMET analysis predicted compliance with all identified compounds, suggesting their suitability as oral drug candidates. The in vitro cytotoxicity assay against MCF-7 cells yielded a moderate cytotoxic classification with an IC50 of 192.90 ?g/mL. These findings highlight the promising potential of E. sumatrensis as a source of bioactive compounds for developing novel anti-breast cancer drugs. However, further research is needed to explore its full therapeutic potential and facilitate its development into pharmaceutical products.